Science as a counter to the erosion of truth in society. - Collins, Harry (Synthese, 2023)
The role of scientific values has taken on new urgency with recent changes in the politics of Western societies. The threat is the erosion of the distinction between true and false in political circles. This could rapidly lead to democracy sliding into populism thence fascism. In the light of this, philosophy and sociology of science should themselves re-examine their role. The main point of the paper is to argue that science could and should push against the erosion of truth in society. Sociological thinking has sometimes tended to erode the difference between science and ordinary thought but it should no longer ignore the political consequences and should, instead, start to take scientific values as a positive resource in society. The philosophical analysis of scientific values, which I will refer to as ‘scientific value analysis, or ‘SVA’, has championed the impact of societal values on science but should also look at the way scientific values could positively affect societal values.